A systematic review and meta-analysis of the long-term effects of physical activity interventions on objectively measured outcomes - J. Gasana; T. O'Keeffe; T. M. Withers; C. J. Greaves (BMC, 2023)
Abstract Background Although physical activity interventions are frequently reported to be effective, long-term changes are needed to generate meaningful health benefits. There are criticisms that evaluations of physical activity interventions mostly report short-term outcomes and that these are often self-reported rather than measured objectively. This study therefore aimed to assess the long-term (at least 24 month) effectiveness of behavioural interventions on objectively measured physical activity. Methods We conducted a systematic review with a meta-analysis of effects on objectively measured physical activity. We searched: Cochrane CENTRAL, EMBASE, PsychInfo, CINAHL and Pubmed up to 10th January 2022. Studies were included if they were in English and included a physical intervention that assessed physical activity in the long-term (defined as at least 24 months). Results Eight studies with 8480 participants were identified with data suitable for meta-analysis. There was a significant effect of interventions on daily steps 24 months post baseline (four studies, SMD: 0.15, 95% CI: 0.02 to 0.28) with similar results at 36 to 48 months of follow up (four studies, SMD: 0.17, 95% CI: 0.07 to 0.27). There was a significant effect of interventions on moderate-to-vigorous physical activity 24 months post baseline (four studies, SMD: 0.18 95% CI: 0.07 to 0.29) and at 36 to 48 months (three studies, SMD: 0.16 95% CI: 0.09 to 0.23). The mean effect size was small. However, the changes in moderate-to-vigorous physical activity and steps per day were clinically meaningful in the best-performing studies. Conclusion This review suggests that behavioural interventions can be effective in promoting small, but clinically meaningful increases in objectively measured physical activity for up to 48 months. There is therefore a need to develop interventions that can achieve greater increases in long-term physical activity with greater efficiency.